2021
DOI: 10.1021/acs.nanolett.1c01359
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Semiconducting Polymer Nanoparticle for Reliable Photoacoustic Imaging of Pneumonia-Induced Vulnerable Atherosclerotic Plaque in Vivo

Abstract: Acute pneumonia can greatly increase the vulnerable risk of atherosclerotic plaque and contribute to the mortality of cardiovascular disease. To accurately assess the rupture risk caused by acute pneumonia, we developed a novel kind of ratiometric semiconducting polymer nanoparticle (RSPN) for photoacoustic imaging of vulnerable plaque in apolipoprotein E-deficient mice complicated with pneumonia. Specifically, RSPN can react with O2 •– and exhibit the enhanced photoacoustic signals at about 690 nm, while 800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…In consideration of this, our study assesses a range of attributes associated with accelerated atherosclerosis and progression to plaque vulnerability, providing comparison between post-infection and PBS-inoculated mice to highlight plaque characteristics and inflammatory changes in the aorta and heart imposed by a low-dose pneumonia infection. In a comparable ApoE−/− mouse study, vulnerable plaque was assessed by oxidative stress based on plaque oxygen concentration 38 . The study utilised ratiometric semiconducting polymer nanoparticle (RSPN) photoacoustic imaging to compare lipopolysaccharide caused pneumonia in ApoE −/− mice to non-infected ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of this, our study assesses a range of attributes associated with accelerated atherosclerosis and progression to plaque vulnerability, providing comparison between post-infection and PBS-inoculated mice to highlight plaque characteristics and inflammatory changes in the aorta and heart imposed by a low-dose pneumonia infection. In a comparable ApoE−/− mouse study, vulnerable plaque was assessed by oxidative stress based on plaque oxygen concentration 38 . The study utilised ratiometric semiconducting polymer nanoparticle (RSPN) photoacoustic imaging to compare lipopolysaccharide caused pneumonia in ApoE −/− mice to non-infected ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…[66] Thus, Zhang and co-workers selected •O 2 − as a response target and constructed ratiometric semiconducting polymer nanoparticles (RSPNs) for photoacoustic (PA) imaging of vulnerable atherosclerotic plaques in vivo (Figure 3a). [67] The RSPN employed the difference in PA signal intensity variation c) Reproduced with permission. [67] Copyright 2021, American Chemical Society.…”
Section: Ros-responsive Imaging Strategymentioning
confidence: 99%
“…[ 66 ] Thus, Zhang and co‐workers selected •O 2 − as a response target and constructed ratiometric semiconducting polymer nanoparticles (RSPNs) for photoacoustic (PA) imaging of vulnerable atherosclerotic plaques in vivo ( Figure a). [ 67 ] The RSPN employed the difference in PA signal intensity variation between •O 2 − ‐responsive molecule (ORM) and •O 2 − ‐insensitive molecule (OIM) under an excitation of 690 and 800 nm, respectively. They found that the PA 690 /PA 800 ratio of RSPN had a positive correlation with the •O 2 − level.…”
Section: Targeting Strategies For the Imaging Of Vulnerable Atheroscl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al developed ratiometric semiconducting polymer NPs (RSPNPs) which exhibited enhanced photoacoustic signals at about 690 nm after reaction with O 2 •– , whereas the signal at 800 nm served as an internal photoacoustic reference. 121 Experiments with apolipoprotein E-deficient mice indicated that RSPNPs could be used to evaluate the rupture risk of atherosclerotic plaques caused by acute pneumonia by determining the oxidative stress level within aortic atherosclerosis. Wang et al developed herceptin-conjugated Poly (lactide-co-glycolic acid)-Polyethylene glycol (PLGA-PEG) NPs loaded with SiO 2 -coated gold nanorods and perfluorohexane liquid as therapeutic agent for laser-induced vaporization treatment and therapy of HER2-positive breast cancer.…”
Section: Imaging Techniquesmentioning
confidence: 99%